Age determination in dog puppies by teeth examination: legal, health and welfare implications, review of the literature and practical considerations - Roccaro, Mariana; Peli, Angelo (Veterinaria Italiana, 2020)
Age determination of puppies represents a significant issue of animal welfare and forensic medicine, particularly for what concerns trade and imports of dogs. Despite the movement of puppy dogs before the age of 15 weeks is forbidden by Regulation (EU) No 576/2013, the occurrence of illegal transport of younger puppies is not uncommon. The illegal trade of puppies increases instances of falsified documentation, the counterfeit of vaccine certificates and discrepancies between the declared age and the real age of the puppies. Consequently, determining the exact age of animals and evaluating their welfare become legally crucial. Dental examination currently represents the most common approach to estimate the age of a puppy in clinical practice and in forensic investigations. In this work we addressed the legal, health and welfare issues associated with dogs’ trade and import and we reviewed the existing literature referring to the assessment of age in dogs by dental examination. The imprecision and inaccuracy of this method make it poorly convincing in legal proceedings. The reasons for such vagueness are to be ascribed both to the lack of standardization and to many variability factors (size, breed, sex, diet, etc.) which influence dental eruption and development.